Appearance of extractives matter as oil-form on wood surface has been causing problems in wood working, especially for laminated wood products and finishing. The problem of extractives on the oily keruing was observed to get the way how to overcome it so the wood utilization able to be increased by laminated wood manufacturing. The effect of the treatments on the oily keruing as laminated wood material has been done by boiling in the water, boiling in diesel fuel and cooking oil mixture, and pre - Jamaludin MALIK; Mochamad Isa ISKANDAR (Jurnal Ilmu dan Teknologi Hasil Hutan, 2009)
Appearance of extractives matter as oil-form on wood surface has been causing problems in wood working, especially for laminated wood products and finishing. The problem of extractives on the oily keruing was observed to get the way how to overcome it so the wood utilization able to be increased by laminated wood manufacturing. The effect of the treatments on the oily keruing as laminated wood material has been done by boiling in the water, boiling in diesel fuel and cooking oil mixture, and press-vacuum with paraffin addition. Comparison was done for inter-treatment and also to non oily keruing. The materials used were oily (Dipterocarpus gracilis), non oily (Dipterocarpus grandifloris) keruing and tannin-base glue. The observed parameters consist of visual appearance, moisture content, density, bonding strength and delaminating. Results indicated that moisture content of all treatment were not more than 15%, density range of 0.71-0.91 g/cm3 and average 0.79 g/cm3. The bonding strength of laminated wood ranges varied from 17.80 kg/cm2 to 37.73 kg/cm2 nd average 26.44 kg/cm2 (dry testing) and 1.81 kg/cm2-13.97 kg/cm2 and average 9.15 kg/cm2 (wet testing), while the delaminating ranges of 41.19% to 52.85% and average 45.52%. Generally, the treatment of boiling in mixture of diesel fuel and cooking oil with 6 : 1 in proportion, resulted increasing properties for laminated wood made of oily keruing.   Keywords : Extractives, oily keruing, tannin, laminated wood